Barriers self-efficacy and performance of creative industry SME: The role of accounting information system - Diana, Nur; Soetjipto, Budi Eko; Handayati, Puji; Restuningdyah, Nurika (The Economics and Finance Letters, 2025)
This research aimed to understand the effects of the accounting information system (AIS) and barriers self-efficacy on small and medium-sized enterprise (SME) performance. A total of 243 SME owners and managers participated in a cross-sectional survey using a questionnaire. Furthermore, the data was collected using a purposive sampling method as part of an explanatory causality investigation. For complex models, structural equation modeling (SEM) was used and was suitable for estimating the data. The results of this study showed that business strategy significantly impacted SME performance and AIS usage. Additionally, AIS usage indirectly affected SME performance through barriers self-efficacy as a mediator. SME performance was also directly proportional to the confidence of actors in overcoming obstacles, while barriers self-efficacy increased the influence of AIS. Furthermore, the inability to deal with accounting and finance issues could be explained by barriers self-efficacy through the elaboration of theories. The use of the theory aligned with the empirical problems and could help solve the obstacles. In conclusion, stakeholders were supported in decision-making to enhance modulation and the use of AIS for sustainable SME management. AIS provided the knowledge needed to make better choices about the goods and services supplied to utilize AIS efficiently.